Thrixspermum indicum (Orchidaceae), a new species from Northeast India - Kumar, Vikas; Verma, Durgesh; Rao, Abbareddy Nageswara (Phytotaxa, 2017)
A new species Thrixspermum indicum is described and illustrated from Northeast India. It is allied to T. carnosum, T. muscaeflorum and T. trichoglottis but quite distinct from all these species in having broadly triangular lateral lobes of lip with acute incurved tips and absence of hairs on the inner surface, margins of mid-lobe and side lobes of lip.